Analisa Biaya Penggunaan Bersama Jaringan Transmisi Kawasan BTDC Nusa Dua - putra, mahadi; Giriantari, Ida Ayu Dwi; Ariastina, Wayan Gede (Majalah Ilmiah Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i01.P18, 2018)
Around the world the deregulation of the electricity business sector has changed from a centralized and integrated into a segmented industry based on the competence of the business people. The new form of trade with free access to transmission and distribution channels has encouraged a competitive trade between consumers and plant owners. In such environments, the transmission network is considered a key factor in the electricity market. Utilization of other companies' transmission to distribute electric power is commonly known as PBJT or Wheeling Transaction. The term PBJT in Indonesia is known as Joint Transmission Network Usage. There are several methods used to calculate transmission lease cost in this paper are used two cost allocation calculations that allow to apply to Bali electricity system that is, Postage-Stamp Rate method, MW-mile method. In this paper, we will apply the Postage Stamp Rate and MW-mile method of Wheeling Transaction in order to obtain the calculation of transmission lease cost acceptable by both parties. Keywords- Transmission, PBJT, Wheeling Transaction, Postage-Stamp Rate, MW-mile